2023
DOI: 10.2166/hydro.2023.096
|View full text |Cite
|
Sign up to set email alerts
|

Novel application of robust GWO-KELM model in predicting discharge coefficient of radial gates: a field data-based analysis

Abstract: Accurate determination of discharge capacity in radial gates as commonly designed check structures is of great importance in hydraulic engineering research. The discharge coefficient plays the most dominant role in calculating the flow discharge through the radial gates. The main goal of this study is to adopt Grey Wolf Optimization-based Kernel Extreme Learning Machine (KELM-GWO) to further improve the prediction accuracy of the discharge coefficient of radial gates. To compare the supreme performance of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The research proved that the model had excellent performance compared with Support Vector Machine (SVM) and Gaussian Process Regression (GPR). However, there were still efficiency problems [18].Aiming at the ECG signal separation problem in the diagnosis of heart disease, A. Diker et al proposed the differential evolution algorithm combined with ELM's hidden neurons to solve the accuracy problem of ELM classification. The experimental results showed that the accuracy rate reached 83.12%, which still had a large optimization space [19].…”
Section: Introductionmentioning
confidence: 99%
“…The research proved that the model had excellent performance compared with Support Vector Machine (SVM) and Gaussian Process Regression (GPR). However, there were still efficiency problems [18].Aiming at the ECG signal separation problem in the diagnosis of heart disease, A. Diker et al proposed the differential evolution algorithm combined with ELM's hidden neurons to solve the accuracy problem of ELM classification. The experimental results showed that the accuracy rate reached 83.12%, which still had a large optimization space [19].…”
Section: Introductionmentioning
confidence: 99%